Sport in Australia a social history (Cambridge Univ. Press, 1994)
Australia is often seen as a sport-obsessed nation, its people besotted with watching and playing sports. This book is an exciting survey of Australia's sporting life since white settlement. It is the first single volume to deal comprehensively with the history of a range of individual sports in Australia including cricket; horse-racing and trotting; netball; rowing and sculling; tennis; lawn bowls; swimming, surfing and surf-lifesaving; and the football codes - Australian rules, rugby league, rugby union and soccer. Leading sports historians look at the impact of professionalism and commercialisation on many sports, the link between sport and nationalism, the successes of Australian sport in the international arena and the effect of the communications revolution on sport. They argue that class prejudice, sexual segregation and racial discrimination have permeated Australia's sporting history, and that sport in Australia has not taken place on a level playing field